(untitled) (Bangladesh Journal of Plant Taxonomy, 2017)
Not available. Keywords: Gonatophragmium mori; Hyphomycetes; Ficus hispida L.; New record. Bangladesh J. Plant Taxon. 24(1): 125127, 2017 (June)